Lady and the trump: Status and wealth in the marriage market - Johan Almenberg; Anna Dreber (Stockholm School of Economics, The Economic Research Institute (EFI), 2008)
We examine a relatively neglected aspect of intergenerational transmission of economic standing, namely culturally determined status markers and their valuation in the marriage market. We take nobility to be such a status marker. Using data on Swedish marriages, we test the hypothesis that nobility have a greater probability of marrying up in terms of wealth. We find a large and statistically significant positive effect for nobility. This finding has important implications for the intergenerational transmission of inequality, and for the longevity of the institution of nobility itself.
Keywords: J11; J12; 330; Marriage; Status; Intergenerational Transmission; Nobility; Ehe; Sozialer Status; Adel; Vermögen; Privater Transfer; Schweden